Grand Canonical Monte Carlo Simulations of Ethanol Conversion to Propylene Over Zeolite Catalysts - Wang, Fangfang; Xia, Wei; Wang, Longxiang; Wang, Junguo; Yang, Xiujie; Chen, Kun (Frontiers in Materials, 2018)
Ethanol conversion reactions were carried out over H-ZSM-5(40) and H-LEV (40) catalysts. For H-ZSM-5 (40), the yield of propylene was almost constant at 20 % during continuous experiments for 8 h. Higher initial propylene yield reached 31 % over H-LEV (40) catalyst. However, there is almost no propylene obtained over H-LEV (40) catalyst after 2 h. Results show that H-ZSM-5 (40) catalyst exhibited higher stability than H-LEV (40). The lower stability of H-LEV (40) is probably due to coke deposition. Grand Canonical Monte Carlo simulations were used to understand how the two zeolites affect their adsorption performance in the ethanol conversion reaction. The isosteric heat of ethylene in ZSM-5(40) zeolite at 303 K has been calculated to verify the rationality of model construction and simulation parameters. It is found that the adsorption of ethanol, ethylene and propylene in H-LEV(40) was stronger, which led to the more difficult desorption of products and higher content of coke deposition. A strong adsorption of reactants and products in H-LEV should be avoided in order to prevent the formation of coke. The simulation results are consistent with the experimental results.